ROLE OF L-ARGININE SUPPLEMENTATION IN PREVENTING OBESITY "ULTRAHISTOCHEMCIAL STUDIES" - Hassan, Safia Mohammed (European Scientific Journal, ESJ, 2013)
Obesity is an important complex and chronic disease. Dietary arginine (2-amino 5-guanidinovaleric acid) supplementation represents a potentially novel and useful strategy for the management of obesity and diabetes. Oral supplementation with L-arginine reduced inflammation and oxidative stress associated with high carbohydrate, high fat feeding in rats. The main goal of the present study was to investigate beneficial effects of Larginine in the protection against intoxication on altered peroxisomal enzymes: D-amino acid oxidase (D-AAO) and catalase after high fat diet (H.F.D). 20 male Swiss albino rats (8 w old) were divided into two groups. Group 1: 5 rats (control), Group II a: 15 rats fed on H.F.D for 24 w. Group II b: 10 rats orally administered L-argenine in a dose of 622.14 mg/kg body weight /day for 12 weeks. 5 rats from each group were sacrificed and processed for ultrahistochemical studies of D-AAO and catalase enzymes. Our results revealed that in addition to lipid accumulation, the formation of myelin figures are related to impaired lipid degradation. After L-arginine supplementation, we observed that EM sections of liver have shown the formation of a peroxisomal reticulum at early times and the subsequent return of single peroxisome (PO). Also, we showed that following H.F.D, PO underwent significant changes in size, shape, and their contents of DAAO and catalase. After L-arginine treatment of animals receiving H.F.D, D-AAO and catalase activities returned to nearly control levels. This recovery could be attributed to capability of L-arginine to alter the antioxidant defense system induced by H.F.D.